Morfologi Insang Ikan Lele Mutiara (Clarias gariepinus Burchell, 1822) yang Diberi Paparan Mikroplastik Polietilen (PE) pada Pakan - Nurul Suwartiningsih; Glady Sunggoro; Raffly Muhammad Dhiaulhaq; Lyly Nur Indah Sari; Kurnia Suci Maharani; Ichsan Luqmana Indra Putra; Haris Setiawan (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Microplastics in the body of fish can damage the function of organs. One of the aquatic biota that can be affected by microplastics is Mutiara catfish. The study aimed to compare the gill morphology of Mutiara catfish after being exposed to microplastics. This study was an experimental study consisting of four treatments, feed treatment with microplastic added with a weight of 0.00 mg/0.75 g feed (control); 0.01 mg/ 0.75 g feed (P1); 0.1 mg/0.75 g (P2); and 1 mg/0.75 g (P3). Each treatment was repeated seven times (seven buckets) and each bucket was filled with five fish so that a total of 140 fish were used. The treatment was carried out for 28 days. Observation of growth parameters was carried out on the entire population, 140 fish, while organ preparation was carried out on a sample of three fish from each treatment. Fish samples were taken using a stratified random sampling technique. Research parameters include gill weight, primary lamela length (LP) and secondary lamela lenght (LS). The results showed the highest gill weight at control 1.76 ± 0.47 g and the lowest at P1 1.20 ± 0.25 g, although it did not significantly different. The highest gill weight/ body weight at control 0.06 ± 0.02 g and the lowest P1 and P2 0.04 ± 0.00 g, although it did not significantly different. Primary lamela length (LP) was highest at P3 1250.34 ± 294.81 μm and lowest at Control 894.78 ± 399.10 μm, and it was significantly different. Secondary lamela lenght (LS) was highest at P3 33.69 ± 4.34 μm and lowest at P1 29.12 ± 5.29 μm. Among controls, P2 and P3; LS length did not significantly different. Microplastic PE up to 1.00 mg/ 0.75 g of feed does not result in a decrease of gill weight and elongation of secondary lamela, but results in significant lengthening of primary lamela.